Making Sense of Collaborative Writing: A Student-Experience-Based Perspective - Yulhenli Thabran; Dony Efriza; Reny Heryanti (Scope : Journal of English Language Teaching, 2021)
The present study examines four pairs or eight students who wrote their creative writing assignments collaboratively. As opposed to the popular view, which stated that writing is one of the most difficult subjects to learn for EFL students, many studies have reported that collaborative writing (henceforth CW) is regarded as a technique that can improve students’ productive writing skills to a great extent. The researchers would like to see how effective CW was for the students who did their writing assignments with their pairs by employing a qualitative case study to examine the eight students’ experiences in writing their essays and fictional stories. The researchers wanted to know why some students could adapt to this learning model, and others faced some problems or failed to achieve the target of learning outcomes. Opened-ended questionnaire and in-depth interviews are used to elicit data from the students. The first pair was the most successful example of partnership in writing since they opened themselves for critiques and suggestions. In contrast, the second pair had some problems that disturbed their collaboration as they did not seem to open themselves for critiques and suggestions. The third pair failed to do an effective partnership because they could not solve problems that blocked their cooperation right from the beginning. The fourth pair found their way for an effective collaboration when they opened themselves for critiques and suggestions. The success or failure in the partnership heavily depends on each student collaborator's willingness to open themselves for criticism and suggestion.